A reappraisal of the nominal curvature method in the fire design of reinforced concrete columns. (March 2020) - Bamonte, Patrick
A reappraisal of the method based on nominal curvature for designing reinforced concrete columns in fire is proposed, with the focus on the validation of an alternative and widely accepted way of applying the method, which differs from the current provisions of EN 1992-1-2. To this end, a systematic comparison between experimental and numerical results is carried out on a database consisting of 74 columns tested in different laboratories. The comparison shows that the method based on nominal curvature yields conservative estimates of the time to failure. Moreover, the numerical results obtained are reasonably close to those obtained by means of finite element analysis. By contrast, if the method is applied in combination with the simplified methods introduced in EN 1992-1-2, the numerical results are not conservative, with a significant overestimation of the bearing capacity of the columns, and of the time to failure, mainly because of the overestimation of the stiffness by the simplified methods.